Sonography of Arteriovenous Fistulas and Grafts. Issue 4 (10th April 2017) - Pietryga, Jason A.; Little, Mark D.; Robbin, Michelle L.
Abstract: Arteriovenous fistulas (AVFs) and arteriovenous grafts (AVGs) are the vascular accesses of choice for long‐term hemodialysis. Strategies to establish and maintain functioning AVFs and AVGs are essential. In addition to clinical evaluation, ultrasound plays a critical role in the evaluation and maintenance of AVFs and AVGs. AVFs have a high rate of failure to mature which can be reliably diagnosed with ultrasound. Treatable etiologies of the failure to mature can often be diagnosed with ultrasound. Causes of secondary AVG failure can also be diagnosed with ultrasound and treated. AVGs have a relatively short functional life expectancy due to a high rate of AVG thrombosis. Ultrasound is a safe, noninvasive way to diagnose vascular stenosis in both AVFs and AVGs prior to thrombosis, potentially saving the access. Routine surveillance ultrasound of asymptomatic AVFs and AVGs is controversial with conflicting studies on its benefit. Routine surveillance ultrasound of AVFs and AVGs is not common practice.